Music intervention during daily weaning trials—A 6 day prospective randomized crossover trial. (December 2016) - Liang, Zhan; Ren, Dianxu; Choi, JiYeon; Happ, Mary Beth; Hravnak, Marylyn; Hoffman, Leslie A.
Highlights: Having patients listen to their choice of music during daily weaning trials reduced anxiety and dyspnea and produced positive changes in physiologic variables. Duration of daily weaning increased, suggesting this intervention may speed weaning from mechanical ventilation. Providing patient selected music during daily weaning trials is a low-cost, potentially beneficial intervention for patients on prolonged mechanical ventilation. Abstract: Purpose: To examine the effect of patient-selected music intervention during daily weaning trials for patients on prolonged mechanical ventilation. Methods: Using a crossover repeated measures design, patients were randomized to music vs no music on the first intervention day. Provision of music was alternated for 6 days, resulting in 3 music and 3 no music days. During weaning trials on music days, data were obtained for 30 min prior to music listening and continued for 60 min while patients listened to selected music (total 90 min). On no music days, data were collected for 90 min. Outcome measures were heart rate (HR), respiratory rate (RR), oxygen saturation (SpO2 ), blood pressure (BP), dyspnea and anxiety assessed with a visual analog scale (VAS-D, VAS-A) and weaning duration (mean h per day on music and non-music days). Results: Of 31 patients randomized, 23 completed the 6-day intervention. When comparisons were made between the 3 music and 3 no music days, there were significant decreases in RR and VAS-D and a significant increase in daily weaning duration on music days (p < 0.05). A multivariate mixed-effects model analysis that included patients who completed ≥2 days of the intervention (n = 28) demonstrated significant decreases in HR, RR, VAS-A, and VAS-D and a significant increase in daily weaning duration on music days (p < 0.05). Conclusions: Providing patient selected music during daily weaning trials is a simple, low-cost, potentially beneficial intervention for patients on prolonged mechanical ventilation. Further study is indicated to test ability of this intervention to promote weaning success and benefits earlier in the weaning process.